Kepemimpinan Kepala Madrasah dalam Meningkatkan Kinerja Guru dan Mutu Pendidikan pada Madrasah Aliyah Plus Taruna Teknik Al Jabbar Medan - Neliwati; Wan Anwar Fuadi; Indra Sakti Siagian; Raudatun Annisa (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to examine the role of madrasah leadership in improving teacher performance and the quality of education at Madrasah Aliyah Plus Taruna Teknik Al Jabbar Medan. The type of research used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation. Data analysis is conducted through data reduction, data presentation, and conclusion drawing. The validity of the data is tested using methodological triangulation. The research findings indicate that the leadership of the madrasah focuses on improving teacher quality, strengthening the curriculum, and fostering a positive school culture. The conclusion of this study states that participative and transparent leadership can create a conducive educational environment, enhance teacher performance, and produce quality graduates